Factors Affecting Measurement of Salivary Cortisol and Secretory Immunoglobulin A in Field Studies of Athletes - Pritchard, Barry Thomas; Stanton, Warren; Lord, Roger; Petocz, Peter; Pepping, Gert-Jan (Frontiers in Endocrinology, 2017)
Aims: Biological and lifestyle factors, such as daily rhythm and caffeine ingestion, recent infection, and antibiotic intake have been shown to influence measurements of salivary cortisol (SC) and secretory immunoglobulin A (sIgA). Current methodology in unsynchronised, field-based studies does not take these effects into account. Moreover, very little is known about the combined effects of biological and lifestyle factors on SC and sIgA. This study supports development of a protocol for measuring biomarkers from saliva collected in field studies by examining the individual and combined effects of these factors on SC and sIgA. Method: At three time points (start of the pre-season; start of playing season; and end of playing season) saliva samples were collected from the entire squad of 45 male players of an elite Australian Football club (mean age 22.8 ± 3.5 years). At each time point biological and lifestyle factors were determined via a questionnaire, and concentrations of both SC and sIgA via an enzyme linked immuno-sorbent (ELISA) assay of saliva samples. In addition, player times to produce 0.5mL of saliva were recorded. Results: Analysis of covariance (ANCOVA) of the data across the three time points showed that daily rhythm had a more consistent effect than the lifestyle factors of caffeine ingestion, recent infection, and antibiotic intake on SC, but not on sIgA. Data for sIgA and SC concentrations were then adjusted for the effects of daily rhythm and lifestyle factors, and correlational analysis of the pooled data was used to examine the relative effects of these two sources of influence on sIgA and SC. With the exception of time to produce saliva, the biological measures of stress were affected by players’ daily rhythms. When daily rhythm was taken into account the group of lifestyle factors did not have an additional effect. Discussion: It is recommended that future studies measuring SC and sIgA make additional adjustments for the daily rhythm, in particular time since first sight of daylight, as small measurement errors of biomarkers can confound discrimination among study participants.